2019
DOI: 10.1021/acs.langmuir.9b00061
|View full text |Cite
|
Sign up to set email alerts
|

Batch-Scale Preparation of Reverse Janus Emulsions

Abstract: A strategy is proposed to produce novel (W1 + W2)/O reverse Janus emulsions in batch scale simply by one-step vortex mixing. Aqueous two-phase systems (ATPSs), i.e., two immiscible aqueous phases dominated by sodium carbonate and ethanol, respectively, are employed as inner phases and vegetable oil (VO) as continuous phase. The geometry of the Janus droplets, although formed as a result of a kinetic process, is tunable and controllable easily by adjusting the composition of ATPSs based on three-phase diagram. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…[34][35][36] Various shapes and complexities of the droplets have been designed by manipulating the chemical composition, volume ratio, as well as the number of the mixed solutions. [37][38][39] One-step vortex mixing, the simplest type of emulsication on a batchscale, was introduced to produce Janus emulsions by Friberg et al and Guo et al (Fig. 2A).…”
Section: Batch Emulsicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] Various shapes and complexities of the droplets have been designed by manipulating the chemical composition, volume ratio, as well as the number of the mixed solutions. [37][38][39] One-step vortex mixing, the simplest type of emulsication on a batchscale, was introduced to produce Janus emulsions by Friberg et al and Guo et al (Fig. 2A).…”
Section: Batch Emulsicationmentioning
confidence: 99%
“…By precisely adjusting the volume ratio of two oils and surfactant concentration, the anisotropic geometry, such as snowman and dumbbell shapes, and the size of Janus droplets could be designed. [37][38][39]41,42 The Cerberus droplets were produced by mixing three mutually immiscible oils with surfactants in aqueous solution (Fig. 2B(i)).…”
Section: Batch Emulsicationmentioning
confidence: 99%
“…While various authors have reported in detail the structural transitions of emulsions through interfacial tension data, the meta‐state of a JCS has not yet been observed in their studies. [ 33,34 ] Such multicompartment structures can allow for the encapsulation of multiple drugs in separate compartments within a JCS.…”
Section: Figurementioning
confidence: 99%
“…37 Alternative current approaches for the production of complex aqueous emulsions are based on a triggered coalescence of droplets by overcoming of the droplet stabilization potential, e.g. by shearmixing of phase separated aqueous polymer mixtures, 38 or rely on externally triggering a polymer phase-separation inside as-formed emulsion droplets. To this end, an induced mass transfer from the dispersed phase, e.g.…”
Section: Introductionmentioning
confidence: 99%